1997
DOI: 10.1021/jf9609690
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Impact on Fiber Degradation:  Increased Enzymatic Digestibility of Genetically Engineered Tobacco (Nicotiana tabacum) Stems Reduced in Lignin Content

Abstract: Cell wall digestibility, lignin content, and lignin composition were analyzed in transgenic tobacco altered in the expression of the phenylpropanoid biosynthetic enzymes caffeic acid 3-O-methyltransferase (COMT) and L-phenylalanine ammonia-lyase (PAL). Reduction of COMT activity by antisense technology resulted in reduced lignin content accompanied by an increased syringyl (S)/ guaiacyl (G) monomer ratio, as determined by pyrolysis/GC/MS and measurement of lignin methoxyl content by wet chemistry. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 42 publications
1
75
1
2
Order By: Relevance
“…Recently, the use of pyrolysis GC-MS has become routine in agricultura1 chemistry and plant biology research (Mulder and Emons, 1993;Niemann et al, 1993;Boudet et al, 1995) to elucidate differences between lignin assays (Reeves and Galletti, 1993;Hatfield et al, 1994) and for characterization of tobacco lignin in wild-type (Faix et al, 1992) and transgenic plants (Halpin et al, 1994;Sewalt et al, 1997). Pyrolysis is a unique and rapid ligninfingerprinting tool capable of determining lignin monomer composition, but it lacks the capability of thioacidolysis, a commonly used method of lignin analysis, to provide detailed information about lignin-bonding patterns and functionality (Boudet et al, 1995).…”
Section: Genetic Manipulation Of Lignin Composition In Transgenic Tobmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the use of pyrolysis GC-MS has become routine in agricultura1 chemistry and plant biology research (Mulder and Emons, 1993;Niemann et al, 1993;Boudet et al, 1995) to elucidate differences between lignin assays (Reeves and Galletti, 1993;Hatfield et al, 1994) and for characterization of tobacco lignin in wild-type (Faix et al, 1992) and transgenic plants (Halpin et al, 1994;Sewalt et al, 1997). Pyrolysis is a unique and rapid ligninfingerprinting tool capable of determining lignin monomer composition, but it lacks the capability of thioacidolysis, a commonly used method of lignin analysis, to provide detailed information about lignin-bonding patterns and functionality (Boudet et al, 1995).…”
Section: Genetic Manipulation Of Lignin Composition In Transgenic Tobmentioning
confidence: 99%
“…Rather, analysis of lignin methoxyl content and pyrolysis suggested an increased syringyl/guaiacyl ratio. One possible explanation of these results is that monolignol biosynthesis from L-phenylalanine might occur by more than one route, even at the early stages of the core phenylpropanoid pathway, prior to the formation of specific monolignol precursors.There is currently intense interest in modifying the content and / or composition of the cell wall structural polymer lignin as a means of improving the efficiency of the paper pulping process for forest trees or of increasing digestibility of forages for ruminant animals (Whetten and Sederoff, 1991; Boudet and Grima-Pettenati, 1996; Campbell and Sederoff, 1996).Recent studies have concentrated on attempts to downregulate the levels of enzymes involved in the reactions specific for lignin monomer synthesis by expression of homologous or heterologous antisense genes in transgenic plants (Dwivedi et al, 1994;Halpin et al, 1994;Ni et al, 1994; Atanassova et al, 1995;Van Doorsselaere et al, 1995;Sewalt et al, 1997). Although the biosynthetic pathway to lignin monomers is relatively well understood, involving consecutive hydroxylation and O-methylation reactions leading from p-coumaric acid via ferulic acid (the monomethoxylated precursor of the G residues of lignin) to sinapic acid (the dimethoxylated precursor of the S residues of lignin), it has recently been suggested that parallel pathways of monomer hydroxylation and methylation could occur at the level of the COA thioesters (Ye et al, 1994) or even at the level of the aldehydes formed after the first reduction of the COA thioesters (Matsui et al, 1994; Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There also is interest in manipulating lignin concentration and composition in forage grasses, such as alfalfa, because these parameters-lignin concentration in particular-have an effect on digestibility in ruminant animals (Sewalt et al, 1997). There is a high degree of variability in the S:G ratio between species and within single species, and even within individual plants, as a result of genetic, developmental, and environmental parameters.…”
Section: Methylation the Syringyl: Guaiacyl Ratio And The Lignin Bimentioning
confidence: 99%
“…Down regulating the activities of phenylalanine ammonia-lyase and cinnamate 4-hydroxylase reduced lignin concentration and resulted in improved fiber digestibility in transgenic tobacco (Sewalt et al 1997a). In alfalfa, reducing the activities of the methylating enzymes COMT and caffeoyl-CoA O-methlytransferase resulted in only modest changes in lignin concentration and fiber digestibility (Sewalt and Dixon 1997).…”
Section: Biochemistry and Physiologymentioning
confidence: 99%